2022
DOI: 10.3390/rs14040936
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Marine Heatwaves in the Japan/East Sea

Abstract: Marine heatwaves (MHWs) are prolonged discrete events of anomalously warm seawater observed around the world. The occurrence of MHWs in the Japan/East Sea (JES), a middle latitude marginal sea with abundant aquatic resources, has severe impacts on marine ecosystems and human society. We used satellite remote sensing products spanning 1982–2020 to investigate the mean states and variations of JES MHWs. The results show that the JES MHWs occurred twice per year. More than 40% of the MHWs were shorter than the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…8c and 10c). The stratification eventually reduced entrainment cooling in the same region (Wang et al 2022), thereby maintaining warm water conditions. The warming tendencies weakened approximately five days after onset, which was attributed to negative vertical terms, showing relatively stronger Ekman upwelling than the growth period of the MHWs.…”
Section: B Physical Mechanisms Of Mhws In the Four Modesmentioning
confidence: 99%
“…8c and 10c). The stratification eventually reduced entrainment cooling in the same region (Wang et al 2022), thereby maintaining warm water conditions. The warming tendencies weakened approximately five days after onset, which was attributed to negative vertical terms, showing relatively stronger Ekman upwelling than the growth period of the MHWs.…”
Section: B Physical Mechanisms Of Mhws In the Four Modesmentioning
confidence: 99%
“…Wang et al. (2022) also suggested that the increase in marine heatwave in the East Sea region may be explained by ocean dynamics rather than atmospheric forcing. Figures 10d and 10e show the daily mean ocean current and standard deviation of the meridional current.…”
Section: What Causes Positive Trends In Marine Heatwave Longevity And...mentioning
confidence: 99%
“…Instead, we suggest an increasing connection between the ocean current and the N-ES marine heatwave duration in the recent period. Wang et al (2022) also suggested that the increase in marine heatwave in the East Sea region may be explained by ocean dynamics rather than atmospheric forcing. Figures 10d and 10e show the daily mean ocean current and standard deviation of the meridional current.…”
Section: Physical Driver Of Excessive N-es Increases In Marine Heatwa...mentioning
confidence: 99%
“…MHWs are detected when SSTs exceed the 90th percentile threshold and persist for longer than five consecutive days [33]. Here, the 90th percentile threshold varies seasonally because it is defined by an 11 d window centered on the calendar day for the 30 years climatology of the daily SST, meaning that the top 10% of the total 330 d (30 years * 11 d window) for each calendar day are used as the 90th percentile threshold [34].…”
Section: Definition Of Mhwsmentioning
confidence: 99%